Effectiveness rehabilitative therapy and Pridinol Mesylate in low back pain - Lorenza Lauricella; Noemi Calabrese; Dalila Scaturro; Domenico Migliorino; Michele Vecchio; Giulia Letizia Mauro (Frontiers in Medicine)
BackgroundSpondylarthritis is a degenerative disease involving the intervertebral disc, vertebral bodies, and adjacent soft tissues. Treatment aims to slow disease progression and manage symptoms through an interdisciplinary approach. It can be conservative and rarely chirurgic.ObjectiveThis study aimed to evaluate the effectiveness of a rehabilitation combined with Pridinol Mesylate in the treatment of Spondylarthritis in elderly patients in terms of pain resolution, improving disability, and quality of life.Materials and methodsWe conducted a retrospective study on patients with Spondylarthritis. The patients recruited (n = 86) were divided into three groups: the Combined Group (CG:28), who received a rehabilitation combined with Pridinol Mesylate (16 women and 12 men, age 66.4 ± 3.99); the Rehabilitation Group (RG, n = 26), who received only rehabilitation (14 women and 12 men, age 66.2 ± 3.84); and the Drug Group (DG: 32), who received only the administration of the Pridinol(18 women and 14 men, age of 66.3 ± 3.9).ResultsThe results show, at T1 (20 days after treatment) in the CG, statistically significant improvements for the NRS and QBPDS. In the RG, statistically significant improvements were observed only for the QBPDS scale. In the DG group, only pain improvement. At T2 (90 days after treatment), the CG showed improvements in NRS, QBPDS, and (SF-36). The RG and DG showed improvements for NRS and for QBPDS. By Bonferroni method, obtained statistically significant values for CG versus RG and for CG versus DG. No statistical significance was found between RG versus DG.ConclusionTargeted rehabilitation treatment, combined with Pridinol Mesylate, reduced pain and improved disability in lumbar Spondylarthritis both in the short and medium term, with improved quality of life in elderly patients.